2008
DOI: 10.2500/ajr.2008.22.3191
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Trial of Pulsed Nasal Nebulizer in Maximally Dissected Cadavers

Abstract: In all measured indices, the nasal douching method with the squeeze bottle was superior to the PARI sinus nebulizer in highly dissected sinonasal cadaver models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 23 publications
1
41
0
3
Order By: Relevance
“…Only 0.5 ± 0.3% of the nebulizer charge was deposited in the maxillary sinuses, corresponding to around 5% in terms of nasal deposition. These results are consistent with previous studies using a cadaver head (Valentine et al, 2008) or volunteers (Möller et al, 2009) measuring maxillary deposition in a similar range (3-5% in terms of nasal deposition). Similar low deposition results have been obtained in the ethmoid region corresponding to 1.1 ± 0.9% of the nebulizer charge and 11% of the nasal deposition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only 0.5 ± 0.3% of the nebulizer charge was deposited in the maxillary sinuses, corresponding to around 5% in terms of nasal deposition. These results are consistent with previous studies using a cadaver head (Valentine et al, 2008) or volunteers (Möller et al, 2009) measuring maxillary deposition in a similar range (3-5% in terms of nasal deposition). Similar low deposition results have been obtained in the ethmoid region corresponding to 1.1 ± 0.9% of the nebulizer charge and 11% of the nasal deposition.…”
Section: Discussionsupporting
confidence: 93%
“…Based on previous studies (Maniscalco, 2006;Möller et al, 2008Möller et al, , 2009Durand et al, 2001;Valentine et al, 2008), specific nasal jet nebulizers using sound effects are currently the best option for targeting antibiotic aerosols to the site of infection in case of chronic rhinosinusitis. This study demonstrates that aerosols produced by these specific nasal sonic jet nebulizers using sound effect are deposited in the anatomical targets to treat sinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 There is an everincreasing array of products available for nasal irrigation, and only limited direct comparisons have been performed. [5][6][7][8] The aim of this study was to compare the efficacy of 7 commercially available and popular devices on maximally operated cadaveric sinuses under direct visualization.…”
mentioning
confidence: 99%
“…It has been shown that endoscopic sinus surgery improves distribution into the sinuses, with a minimal ostial size of 4 mm needed to begin seeing sinus penetration [14]. Largevolume squeeze bottles or passive flow devices such as the Neti Pot (Himalayan Institute, Honesdale, PA) appear to have the best sinus penetration after endoscopic sinus surgery, with higher volume and pressure likely resulting in the best distribution [15]. It has been estimated that 5% to 37% of topically deposited medications are absorbed by the mucosa, with the rest being removed by mucociliary transport [16].…”
Section: Topical Therapy and Surgical Techniquementioning
confidence: 98%